PEMANTAPAN PERAN PROFESI AKUNTANSI MANAJEMEN DALAM DUNIA BISNIS - Hamfri Djajadikerta (Center for Economic Studies Universitas Katolik Parahyangan, 2005)
In recent years, business environment has change, and it has an effect on management accounting profession. The role of Management Accountant in business has been change from the accounting data provider to a member of top level management team. As an information agent, Management Accountant plays important role in the strategic decision making in business organization.